2022
DOI: 10.3389/fmicb.2022.900690
|View full text |Cite
|
Sign up to set email alerts
|

Cronobacter spp. in Commercial Powdered Infant Formula Collected From Nine Provinces in China: Prevalence, Genotype, Biofilm Formation, and Antibiotic Susceptibility

Abstract: The purpose of this study was to investigate the prevalence of Cronobacter spp. in commercial powdered infant formula (PIF) from nine provinces in China from March 2018 to September 2020, and to reveal the genotype, biofilm-forming ability, and antibiotic susceptibility of these isolates. A total of 27 Cronobacter strains, consisting of 22 Cronobacter sakazakii strains, 3 Cronobacter malonaticus strains, 1 Cronobacter turicensis strain, and 1 Cronobacter dublinensis strain, were isolated from 3,600 commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…A total of eleven Cronobacter serogroups were recognized in this study. C. sakazakii O1 and O2 were the dominant serotypes, in accordance with a previous study from China which investigated commercial powdered infant formula [ 8 ]. Additionally, another previous study showed that C. sakazakii serotypes O1, O2, and O4, and C. malonaticus serotype O2 were particularly significant in clinical cases and were probably related to human infections [ 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A total of eleven Cronobacter serogroups were recognized in this study. C. sakazakii O1 and O2 were the dominant serotypes, in accordance with a previous study from China which investigated commercial powdered infant formula [ 8 ]. Additionally, another previous study showed that C. sakazakii serotypes O1, O2, and O4, and C. malonaticus serotype O2 were particularly significant in clinical cases and were probably related to human infections [ 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…are sensitive to conventional antimicrobials, but the proportion of Cronobacter spp. exhibiting multiple-drug resistance is still increasing year by year [ 8 , 9 ]. Therefore, understanding the prevalence of Cronobacter and its antibiotic resistance in farming systems will help develop effective monitoring systems and contribute to improving public health and help control the spread of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…examined showed resistance genes for beta-lactamases CSA-1 and CMA-1, which was consistent with the observed in vitro resistance to the cephalosporin KF. Since the initial report on the bla CSA and bla CMA gene family responsible for cephalosporin resistance in Cronobacter spp., resistance to KF has been documented in various clinical and environmental strains in different countries worldwide [65][66][67][68][69]. Additionally, we detected the presence of the mrc 9.1 gene, which confers resistance to colistin (polymyxin), considered a gene of significant concern in public health.…”
Section: Discussionmentioning
confidence: 80%
“…Although culture methods are important for Cronobacter spp detection, they are time-consuming and involve complex steps (Chen et al, 2018;Armstrong et al2019). The molecular characteristics of C. sakazakii, which is isolated from powdered milk infant formula and other sources, can be revealed through genotyping, which can also aid in the pathogen's prevention and source tracing (Ling et al, 2021, Fei et al, 2018, Fei et al, 2022. It is now believed that Cronobacter sakazakii is a newly discovered opportunistic bacteria that is frequently isolated from powdered milk infant formula and other foods that usually cause severe morbidity and mortality through some infectious diseases in neonates, infants, and other age groups, and so far, especially in Egypt, limited studies are available on its prevalence rate in foodstuff.…”
Section: Introductionmentioning
confidence: 99%